Effects of Grain Size on the Corrosion and Discharge Behaviors of Mg–Y Binary Alloys for Mg-Air Batteries. Issue 13 (23rd September 2020) - Yang, Huabao; Wu, Liang; Jiang, Bin; Lei, Bin; Liu, Wenjun; Song, Jiangfeng; Huang, Guangsheng; Zhang, Dingfei; Pan, Fusheng
Abstract : The corrosion and discharge behaviors of two Mg-1Y alloys with significantly different grain sizes are studied for application as the anodes for Mg-air batteries in 3.5 wt.% NaCl solution. The correlations between grain size and corrosion and discharge behaviors are also systematically analyzed. The results show that the grain boundaries are the preferential sites for the attack during the electrochemical dissolution of Mg alloys and therefore the Mg-1Y(E) alloy with a fine uniform grain size shows a high corrosion rate and a strong discharge activity in contrast with the Mg-1Y(H) alloy with a large uneven grain size. Furthermore, the Mg-1Y(E) alloy exhibits a steady high discharge voltage at small current density, especially at 2.5 mA cm −2 .